Phenology and rate of sprouting of launaea taraxacifolia (willd.) amin ex c. jeffrey in Ibadan, Oyo state, Nigeria (2020)
Launaea taraxacifolia, a locally consumed vegetable in Nigeria is becoming popular due to the medicinal and nutritional potentials. Information about its agronomical properties is scanty. This study aims to determine the phenology and sprouting behaviour in Ibadan, southwest Nigeria. Studies were conducted at the Crop Garden of Department of Crop Protection and Environmental Biology, University of Ibadan, Nigeria in wet and dry seasons of 2019. Eighteen experimental bags, arranged in completely randomized design, filled with 5 kg each of heat-pretreated soil, and 15 field plots (1 m x 1 m each) in randomized complete block design were used for phenology and rate of sprouting (RS) respectively. Cuttings of 10 cm long of wild rhizomes of Launaea taraxacifolia were nursed for two weeks and transplanted uniformly at one seedling per pot. Planting spacing of 0.25 m x 0.25 m, 0.25 m x 0.5 m, 0.5 m x 0.50 m, 0.45 m x 0.75 m, and 0.55 m x 0.90 m and replicated three times were used. Data obtained were analysed using Analysis of Variance. Significant means were separated using Fisher’s LSD at p<0.05.Launaea taraxacifolia attained 67 - 111.4 cm height at 12 weeks after transplanting (WAT), branching and bolting, flowering and seeds matured at 8, 10, 12 WAT respectively. The means dry weight at 12 WAT in dry and wet seasons were 5.82 and 15.59 g/plant/pot respectively. Multiple sprouting commenced at 2 WAT and maximum RS (3.25/week) was attained at 8WAT in both seasons. Spacing at 0.25 m x 0.50 m was the best. Launaea taraxacifolia phenologically established faster as a good biomass accumulator in wet season unlike dry season. Spacing 0.25 m x 0.50 m was more desirable for Launaea taraxacifolia as it allowed better proliferation